Expression Profiles of CircRNA and mRNA in Lacrimal Glands of AQP5–/– Mice With Primary Dry Eye - Liu, Yaning; Di, Guohu; Hu, Shaohua; Zhao, Tianyu; Xu, Xinkai; Wang, Xiaoyi; Chen, Peng (Frontiers in Physiology, 2020)
Background: Identify the differentially expressed circular RNA (circRNA) and elucidate their potential function in AQP5 knockout (AQP5-/-) mice with primary dry eye phenotype. Methods: A slit lamp examination was performed on AQP5 knockout mice to assess corneal epithelial defect by fluorescein sodium staining. Hematoxylin-eosin staining and transmission electron microscope analysis were performed to access the structure of lacrimal gland epithelial cells. The expression profiles of circRNA and messenger RNA (mRNA) were determined by microarray analysis. The selected circRNA was verified by quantitative real-time reverse transcription polymerase chain reaction (qRT-PCR). Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis were used to predict biological functions and potential pathways of parental genes involved in lacrimal gland epithelial cell changes. According to the bioinformatics analysis of identified circRNA, we can predict a circRNA-miRNA-mRNA network. Results: AQP5-/- mice exhibit spontaneous dry eye symptoms. AQP5 deficiency obviously changes the structure of lacrimal gland epithelial cells. Analysis showed that compared to AQP5+/+ mice, 30 circRNAs in the lacrimal glands of AQP5-/- mice had differential expression (fold change ≥ 2.0, P < 0.05). Nine upregulated circRNAs were identified by qRT-PCR; nine upregulated validated circRNAs, 40 altered microRNAs (miRNAs), and nine upregulated mRNAs were involved in the network analysis. KEGG analysis showed these nine target genes were expressed in phagosomes. Conclusions: AQP5-/- mice have primary and stable dry eye phenotypes from birth. The study identified different expressed circRNAs in lacrimal glands between AQP5-/- and AQP5+/+ mice, predicting a circRNA-miRNA-mRNA network of phagosomes. CircRNA likely plays an important role in lacrimal gland epithelial cell pathogenesis. Therefore, it is reasonable to use circRNA as a potential therapeutic target for dry eyes.